2005
DOI: 10.1161/circulationaha.105.554006
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Validation of a New Ultrasound Method for the Simultaneous Assessment of Radial and Longitudinal Myocardial Deformation Independent of Insonation Angle

Abstract: Background-Strain and strain rate have been proposed as tools to quantify regional myocardial function. One of the major pitfalls of the current methodology is its angle dependency. To overcome this problem, we have developed a new method for the estimation of strain, independent of angle. The aim of this study was to validate this new methodology in an experimental setting using sonomicrometry. Methods and Results-In 5 open-chest sheep, ultrasound data were acquired. The new methodology was used to perform si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
204
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 307 publications
(209 citation statements)
references
References 29 publications
5
204
0
Order By: Relevance
“…Assessment of 2D peak SGLS (%) of the LV was performed with 2D echocardiography and grey scale speckle tracking imaging, using 2-, 3-, and 4-chamber views from the apical long axis, and a frame rate > 50 frames/s [20]. The Lagrange formula (L2L 0 /L 0 ) was used to calculate percent strain [21]. Strain was quantified using GE software (EchoPAC, version 7.0.0, General Electric Vingmed).…”
Section: Study Protocolmentioning
confidence: 99%
“…Assessment of 2D peak SGLS (%) of the LV was performed with 2D echocardiography and grey scale speckle tracking imaging, using 2-, 3-, and 4-chamber views from the apical long axis, and a frame rate > 50 frames/s [20]. The Lagrange formula (L2L 0 /L 0 ) was used to calculate percent strain [21]. Strain was quantified using GE software (EchoPAC, version 7.0.0, General Electric Vingmed).…”
Section: Study Protocolmentioning
confidence: 99%
“…Depending on the direction of deformation, longitudinal, circumferential, and radial S and SR can be measured using TDI or two‐dimensional speckle tracking. Both modalities have been validated against sonomicrometry and cardiac MRI 135 , 136 . Importantly, echocardiographic methods have higher frame rates than cardiac MR and are better suited to study temporal aspects of cardiac function.…”
Section: Strain and Strain Rate In Dhfmentioning
confidence: 99%
“…This poorer outcome could not be explained only by the patients' baseline characteristics, but also because graft PCI was difficult and the lesions were complex and contained more luminal thrombi. 27 In a recent retrospective study by Lei Ge et al, 28 the benefits of PCI with a DES vs. BMS were established for venous graft stenoses (6-month MACE-free survival of 88.5% for DES vs 71.9% for BMS), and the use of BMS was an independent predictor of MACE. In this study, the authors reported a low rate of total occlusions, only 4.3% for DES and 3.3% for BMS, and distal protection devices were used in a third of patients.…”
Section: Prognosismentioning
confidence: 99%